The Analysis of Difficulties in Pronouncing English Vowels (Monophthongs) in Singing English Song - Billy Fernanda Kurniawan Billy; Juita Triana; Andrian Nuriza Johan (Department of English Language Education, Universitas Muhammadiyah Purworejo, Indonesia, 2022)
The aims of this study are to find out the English Vowel (Monopthongs) in Singing English Song which is difficult to pronounce, and to find out the problem that causes the difficulties faced by the students of UKM Surya Sagitta Choir Purworejo Muhammadiyah University. This research is descriptive qualitative research. Then, the researchers take 15 students as a sample of this research, they used pronunciation tests and questionnaires to collect the data. The students’ pronunciations are recorded then analyzed by transcribing the students’ pronunciation into phonetic transcription. Based on the finding and data analysis the researchers find 401 mispronounced English vowels, including 279 mispronounced of English short vowel monophthongs [ɪ], [ɛ], [æ], [ɒ], [ʌ], [ʊ], [ə], and 122 English long vowel monophthongs [i:], [ɑː], [u:], [ɔ:], [ɜ:]. The most vowels that are difficult to pronounce by students are (1) Short vowels [ɪ] which are 143 times (79,4 %) of 12 words analyzed. (2) long vowel [ɜ:] 19 times (63%) of 2 words analyzed. (3) long vowel [ɔ:] 33 times (55%) of 4 words analyzes. Therefore, students have difficulty pronouncing English vowels [ɪ], [ɜ:] and [ɔ:].The factors that cause students’ difficulties in pronouncing English vowels in singing English songs are they rarely listen to English songs, confuse about pronounces, and don’t understand the meaning and lyrics of the song.